Análisis de competitividad entre las empresas JM&A e imagen creativa,en el proceso de diseño y producción de etiquetas para la empresa ecuatoriana laboratorios MAD (2022)
La globalización genera en las empresas el uso de herramientas para evaluar, diagnosticar y mejorar continuamente la productividad, eficiencia en los procesos productivos y a su vez hacer procesos eficaces, sin exonerar el sector de la industria gráfica, interviniendo el proceso de las artes gráficas y la competitividad en este sector económico. El término de artes gráficas engloba varios conceptos, pero principalmente se dedican a ejecutar los procesos artísticos de la creación, elaboración e impresión de un diseño en específico; existen varios medios para aplicar sus técnicas, tales como, rótulos, carteles, packaging (envases, cajas, recipientes, botellas, etc.), etiquetas, libros, revistas e indumentaria. (Escuela de postgrado de arte, artesanía y oficios, 2020) “Al pasar las décadas se evidencia que las artes gráficas como cualquier otra manifestación artística, tiene la finalidad de “expresar” (Reyna, 2020). Es decir, el concepto de “artes gráficas” engloba principalmente el proceso artístico de la creación, elaboración e impresión de un diseño, en este caso se aplica esta técnica al desarrollo de la etiqueta. Considerando lo anteriormente expuesto, esta investigación es el análisis de competitividad entre las empresas JM&A Vs IMAGEN CREATIVA, en el desarrollo de las artes gráficas para las etiquetas de LABORATORIOS MAD, es por ello que es esencial definir el termino de etiqueta, la cual es “una pieza de plástico, madera, tela, papel o pintura que se adhiere a un empaque o envase de cualquier producto y su función básicamente es de facilitar la identificación del producto” (Pérez Benavides, López Bello, Vega Chaparro, & Sánchez Olarte, 2015). JM&A es una empresa Pyme, especializada en la comercialización y producción de suministros gráficos específicamente en etiquetas publicitarias; con 12 años de experiencia, supliendo necesidades del mercado, tales como: distribución de adhesivos propalcotes y vinilos para los distintos sistemas de impresión como offset, impresión digital y serigrafía, Point of Purchase advertising production, and label manufacturing in various presentations, seeking to provide solutions to customer requirements, wholesale wholesale or retail; located in the city of Bogotá (Colombia) in the El Ricaurte neighborhood. JM&A has an added value, providing technical advice prior to the provision of the service, using techniques such as neuromarketing and neurolinguistics. IMAGEN CREATIVA, a company of the artisan regime, with a history of more than 15 years in the Ecuadorian market, offering offset, digital and laser, mainly for the development of graphic arts in relation to labels, in reference to the image, photography and design, working with high standards of quality, having as its main activity the production and marketing of labels, followed by photography around the theme of advertising, marketing, and Point of Purchase (Point of purchase). IMAGEN CREATIVA is a company with human talent of excellent quality and with a Colombian owner who found a potential market in Guayaquil (Ecuador), where the company is located and where for its work with the graphic arts it has managed to position itself in the market.LABORATORIOS MAD is a general regime company, dedicated to the marketing and production of hair care items under the SANOART brand since 2017, being a company that produces its own products and outsources as importer some merchandise, such as shampoos for different types and colors of hair, hair treatments and straightening products - Botox and Keratin; located in the city ​​of Guayaquil (Ecuador). IMAGEN CREATIVA and MAD LABORATORIES have a commercial relationship since 2000, covering Point of Purchase advertising and the development of the graphic arts of labels for its cosmetic products until the year 2018. The company JM&A since this year develops the graphic arts of labels for the MAD LABORATORIES products.Analyzing the corporate qualities of the JM&A company, this research is disposes to identify the possibilities that it has to carry out the entire process of graphic arts of the labels (pre-print, print and post-print) of the company MAD LABORATORIES. The monograph will be developed under the qualitative research method and with descriptive approach, in order to carry out an analysis of competitiveness only among the two suppliers: JM&A and IMAGEN CRATIVA, for the acquisition of all the services of graphic arts, of the labels on the products that the company sells MAD LABORATORIES at Ecuador. Given the above, interviews will be implemented as an information collection technique, likewise, documentary information and investigative each of the companies